2015
DOI: 10.1194/jlr.m054874
|View full text |Cite
|
Sign up to set email alerts
|

Human monocyte-derived dendritic cells turn into foamy dendritic cells with IL-17A

Abstract: The emerging fi eld of research called immunometabolism results from mutual interactions between metabolism and immune system. Chronic infl ammation and changes in immune cells participate in metabolic disorders such as atherosclerosis, type 2 diabetes mellitus, and obesity ( 1 ), which are now consequently considered both metabolic and chronic infl ammatory diseases. Conversely, the physiopathological remodeling of cell-intrinsic metabolic pathways modulates the functions of immune cells ( 1, 2 ).Macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
13
1
Order By: Relevance
“…IL-17A is considered to be proatherogenic and is found to be involved in the formation of foamy macrophages 22 . Recently Salvatore et al found that IL-17A turned monocyte derived dendritic cells into foamy dendritic cells by increased cholesterol uptake 23 . Here, in-vitro studies on keratinocytes were further validated on psoriatic skin and we found elevated levels of cholesterol in psoriatic lesional skin and decreased expression of cholesterol and fatty acid related genes.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A is considered to be proatherogenic and is found to be involved in the formation of foamy macrophages 22 . Recently Salvatore et al found that IL-17A turned monocyte derived dendritic cells into foamy dendritic cells by increased cholesterol uptake 23 . Here, in-vitro studies on keratinocytes were further validated on psoriatic skin and we found elevated levels of cholesterol in psoriatic lesional skin and decreased expression of cholesterol and fatty acid related genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that IL‐17 stimulation increases the expression of Msr‐1 and other genes related to lipid metabolism, increasing the number of LDs. However, IL‐17 stimulation did change the expression of MHC proteins . Similarly, the accumulation of TAG in dendritic cells stimulated with tumor explant supernatants was dependent on its uptake mediated by Msr‐1, which was increased in dendritic cells from tumor‐bearing mice.…”
Section: Lds and Antigen Presentationmentioning
confidence: 91%
“…However, IL-17 stimulation did change the expression of MHC proteins. 204 Similarly, the accumulation of TAG in dendritic cells stimulated with tumor explant supernatants was dependent on its uptake mediated by Msr-1, which was increased in dendritic cells from tumor-bearing mice. In this work, the authors showed that dendritic cells generated from Msr-1 −/− mice failed to accumulate lipids after transfer to tumor-bearing recipients and were more effective in Tcell activation.…”
Section: Lds and Antigen Presentationmentioning
confidence: 93%
“…These studies demonstrated an increase in the expression and production of cytokines resulting from the interaction of macrophages with modified lipoproteins. Accumulating evidence suggested that it is likely that some pro-inflammatory cytokines may be involved in the formation of foam cells [44][45][46]. Moreover, here, we included further experiments testing the knockdown effect of five pro-inflammatory molecule-encoding genes identified in our previous study [19], such as IL15, EIF2AK3, F2RL1, TSPYL2, and ANXA1, on LDL accumulation, that can help to elucidate the relationship between the inflammatory immune response and the accumulation of cholesterol during the formation of foam cells (Figure 4).…”
Section: Discussionmentioning
confidence: 99%